Performance evaluation of TCP/IP traffic over ABR service - Maung Hla Min. (2008)
This project is to study the performance of Transmission Control Protocol (TCP) traffic when it is running on top of the ABR service. First, we will investigate the ABR traffic management and flow control which include the connection parameters, service categories, congestion control schemes and switch dropping policies. Then we will go into the TCP congestion control mechanisms, which in specific, include slow start, congestion avoidance, fast retransmit and fast recovery. We will discuss the advantages and disadvantages of using TCP Tahoe, TCP Reno and TCP Vegas congestion control mechanisms. We will also discuss other TCP control mechanisms, such as selective acknowledgment and modified fast retransmit mechanism, which can enhance the throughput and can recover effectively from multiple packets loss. Finally the OPNET simulation tool is used to evaluate the performance of different control mechanisms and to determine the minimum switch buffer requirement in order to achieve maximum throughput.